Keamanan Jajanan Anak Sekolah Dasar: Studi Mikrobiologis dan Kimiawi di SD 008 Awang Long Samarinda - Rudy Agus Riyanto (Jurnal Skala Kesehatan, 2026)
The safety of school children's snacks is a crucial issue in supporting children's growth and development and in preventing foodborne diseases. Snacks that do not meet food safety standards may contain microbiological contaminants and hazardous chemicals that can negatively affect children's health. This study aimed to evaluate the microbiological and chemical safety of snacks sold at the canteen of SD 008 Awang Long in Samarinda, Indonesia. This descriptive observational study involved eight snack samples collected from different vendors in the school canteen. Microbiological tests for Escherichia coli and Salmonella were conducted using the multiple-tube fermentation technique, while tests for borax and formalin were performed qualitatively using rapid reagent test kits. Laboratory analyses were conducted at the Regional Health Laboratory of Samarinda from February 25 to March 2, 2025. Results were interpreted based on the Indonesian Food and Drug Authority Regulation (BPOM) No. 13 of 2019 concerning Food Quality Requirements. All snack samples tested negative for E. coli (<3.6 MPN/g) and Salmonella. Two selected samples—meatball skewers and vermicelli—also tested negative for borax and formalin. The snacks sold at SD 008 Awang Long met food safety standards in terms of both microbiological and chemical parameters. However, continuous monitoring and education for food vendors and school staff are recommended to ensure the sustained safety and quality of school children's snacks.